Synthesis of PbI2 Single‐Layered Inorganic Nanotubes Encapsulated Within Carbon Nanotubes. (16th December 2013) - Cabana, Laura; Ballesteros, Belén; Batista, Eudar; Magén, César; Arenal, Raúl; Oró‐Solé, Judith; Rurali, Riccardo; Tobias, Gerard
<x xml:space="preserve">Abstract</x> The template assisted growth of single‐layered inorganic nanotubes is reported. Single‐crystalline lead iodide single‐layered nanotubes have been prepared using the inner cavities of carbon nanotubes as hosting templates. The diameter of the resulting inorganic nanotubes is merely dependent on the diameter of the host. This facile method is highly versatile opening up new horizons in the preparation of single‐layered nanostructures. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>